Integration of Ethnomathematics-Project-Based-Learning to Enhance Understanding of Geometric Transformations - Kesumawati, Nila; Ningsih, Yunika Lestaria; Octaria, Dina; Rohana (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
Transformation geometry is an important topic in mathematics education. However, undergraduate instruction is often abstract and focused on procedures, which limits students’ conceptual understanding. Project-Based Learning and ethnomathematics are known to support meaningful learning. Nevertheless, studies that integrate ethnomathematics into a Project-Based Learning framework for teaching transformation geometry in mathematics education programs are still limited. This study aims to develop and evaluate an ethnomathematics-based PjBL model to improve students’ understanding of transformation geometry. The research employed a research and development (R&D) approach using the ADDIE model, encompassing the Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted with second-year undergraduate students enrolled in a Transformation Geometry course in the Mathematics Education program at Universitas PGRI Palembang. Ethnomathematical contexts drawn from local cultural practices, such as weaving patterns, wood carving motifs, and traditional architecture, were integrated into project-based learning activities. Data were collected through expert validation sheets, pretest–posttest instruments, observation sheets, and student response questionnaires. The results indicate that the developed learning model is valid, as evidenced by expert assessments of content, pedagogy, and media; practical, based on high levels of implementation and positive student responses; and effective, as shown by significant improvements in students’ transformation geometry learning outcomes. These findings suggest that integrating PjBL with ethnomathematics offers a contextually grounded and pedagogically robust approach to enhancing conceptual understanding of transformation geometry at the undergraduate level. Abstrak Geometri transformasi merupakan topik penting dalam pendidikan matematika. Namun, pembelajaran pada jenjang perguruan tinggi masih sering bersifat abstrak dan berfokus pada prosedur, sehingga membatasi pemahaman konseptual mahasiswa. Project-Based Learning dan etnomatematika telah dikenal mampu mendukung pembelajaran yang bermakna. Meskipun demikian, penelitian yang mengintegrasikan etnomatematika ke dalam kerangka Project-Based Learning untuk pembelajaran geometri transformasi pada program pendidikan matematika masih terbatas. Penelitian ini bertujuan untuk mengembangkan dan mengevaluasi model Project-Based Learning berbasis etnomatematika guna meningkatkan pemahaman mahasiswa terhadap geometri transformasi. Penelitian ini menggunakan pendekatan penelitian dan pengembangan (Research and Development) dengan model ADDIE yang meliputi tahap analisis, perancangan, pengembangan, implementasi, dan evaluasi. Penelitian dilaksanakan pada mahasiswa semester dua yang mengikuti mata kuliah Geometri Transformasi pada Program Studi Pendidikan Matematika di Universitas PGRI Palembang. Konteks etnomatematika yang bersumber dari praktik budaya lokal, seperti motif tenun, ukiran kayu, dan arsitektur tradisional, diintegrasikan ke dalam kegiatan pembelajaran berbasis proyek. Data dikumpulkan melalui lembar validasi ahli, instrumen pretest–posttest, lembar observasi, dan angket respons mahasiswa. Hasil penelitian menunjukkan bahwa model pembelajaran yang dikembangkan bersifat valid berdasarkan penilaian ahli terhadap aspek materi, pedagogik, dan media; praktis berdasarkan tingkat keterlaksanaan yang tinggi dan respons positif mahasiswa; serta efektif yang ditunjukkan oleh peningkatan hasil belajar geometri transformasi mahasiswa secara signifikan. Temuan ini menunjukkan bahwa integrasi Project-Based Learning dengan etnomatematika menawarkan pendekatan pembelajaran yang kontekstual dan kuat secara pedagogis untuk meningkatkan pemahaman konseptual geometri transformasi pada jenjang perguruan tinggi.